Characterization of Agarolytic Pathway in a Terrestrial Bacterium Cohnella sp. LGH - Li, Gen; Guo, Rui; Wu, Shuqi; Cheng, Si; Li, Jiaqi; Liu, Zhenzhen; Xie, Wangliang; Sun, Xiaolin; Zhang, Qiuyi; Li, Zihan; Xu, JiaZheng; Wu, Jun; et al. (Frontiers in Microbiology, 2022)
Previously, we have reported an endo-type β-agarase AgaW responsible for the hydrolysis of agarose into the major product neoagarotetraose in a terrestrial agar-degrading bacterium Cohnella sp. LGH. Here, we identified and characterized the following depolymerization pathway in strain LGH through the genomic and enzymatic analysis. In the pathway, neoagarotetraose was depolymerized by a novel α-neoagarooligosaccharide (NAOS) hydrolase CL5012 into 3,6-anhydro-α-L-galactose (L-AHG) and agarotriose; Agarotriose was further depolymerized by a novel agarolytic β-galactosidase CL4994 into D-galactose and neoagarobiose; Neoagarobiose was finally depolymerized by CL5012 into L-AHG and D-galactose. Unexpectedly, although α-agarase has not been identified in strain LGH, the combined action of CL5012 and CL4994 indeed plays a critical role in the depolymerization of agarotetraose, one theoretical product of α-agarase hydrolysis of agarose. In this pathway, agarotetraose was depolymerized by CL4994 into D-galactose and neoagarotriose; Neoagarotriose was then depolymerized by CL5012 into L-AHG and agarobiose. Furthermore, another novel endo-type β-agarase CL5055 was identified as an isozyme of AgaW with different pH preference in the hydrolysis of agarose into α-NAOSs. Strain LGH seemed to lack a common exo-type β-agarase responsible for the direct depolymerization of agarose or neoagarooligosaccharide into neoagarobiose. These results highlighted the diversity of agarolytic manner in bacteria and provided a novel insight on diversity of agarolytic pathways.